The Effect of Trust in Social Media and E-Commerce Companies on Consumer Decision - Tuğçenur Ekinci Furtana; Hasan Özkazanç (İktisat Politikası Araştırmaları Dergisi)
Today, due to technological developments, the speed at which shopping takes place in the virtual environment is increasing. In the social media environment, companies follow technological developments and carry out harmonisation studies in order to gain a competitive advantage. By focusing on consumer demands and needs, this research shows how sales are expected to increase as consumer needs and expectations are met. This research also aims to reveal the effect on consumer decisions as a sense of trust is created in consumers while shopping via e-commerce. This study uses a quantitative research method, and the questionnaire prepared for this purpose was applied to 409 participants with social media accounts. Research data were analysed using IBM SPSS 22.0. Reliability analysis, descriptive statistical analysis, independent sample t test, anova test, correlation and simple linear regression were applied to the obtained data. The results of this analysis showed that there is a positive and significant relationship between platform reliability, brand trust, brand loyalty and purchase intention in e-commerce.